2015
DOI: 10.5958/2231-6701.2015.00021.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tank Silt Application on Productivity and Economics of Maize-Based Production System in Southern Rajasthan

Abstract: Water tanks are an integral part of village settlements in southern Rajasthan. Runoff water carries along nutrients and fine organic matter particulates from agricultural lands. Often the sources and pathways of nutrients moved by sediments in the runoff are difficult to fully identify and assess the losses. In rainfed farming system, there is a need to capture significant amount of rainwater, which is generally lost as runoff and deep drainage. This stored water can be used for supplemental irrigation, increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Whereas, application of TS coupled with fertilizer N had a positive impact even in winter season. Both direct and residual influence of TS application varied according to soil texture and availability of soil moisture as well as with growing practices of Kharif and Rabi crops (Sharma et al, 2015). Returning of TS rich in microbial biomass into the soil would and crop production (Tiwari et al, 2014) which is a potential strategy for restoring degraded Alfisols.…”
Section: Residual Effect On Horsegram Biomass Productionmentioning
confidence: 99%
“…Whereas, application of TS coupled with fertilizer N had a positive impact even in winter season. Both direct and residual influence of TS application varied according to soil texture and availability of soil moisture as well as with growing practices of Kharif and Rabi crops (Sharma et al, 2015). Returning of TS rich in microbial biomass into the soil would and crop production (Tiwari et al, 2014) which is a potential strategy for restoring degraded Alfisols.…”
Section: Residual Effect On Horsegram Biomass Productionmentioning
confidence: 99%
“…These maps of tank silt application might also provide inputs for agronomic modelling as tank silt application brought out an increase in the productivity of different cropping systems (Sharma et al, 2015), and organic carbon and available nutrient status (Patil et al, 2017). It might also provide inputs for hydrological modelling as tank silt application has been demonstrated to increase available water capacity (Deshmukh et al, 2019).…”
Section: Futures Studiesmentioning
confidence: 99%
“…The tank silt samples also had higher counts of bacteria, actinomycetes and fungi 65 . Sharma et al 66 reported (experiments conducted on ten farmers' fields in 1 ha land) that application of tank silt with improved management practices recorded an increase of 36.6% in maize grain yield over non-application of tank silt. Application of tank silt also benefited subsequent crop grown during rabi season and produced a significant residual response in maize-wheat, maizemustard and maize-taramira cropping systems.…”
Section: Tank Siltmentioning
confidence: 99%